2005
DOI: 10.1892/0891-6640(2005)19[865:psosap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies of Serum Acute-Phase Protein Concentrations in Hematologic and Neoplastic Diseases of the Dog

Abstract: Serum concentrations of acute-phase proteins (APPs): haptoglobin (Hp), ceruloplasmin (Cp), serum amyloid A (SAA), and C-reactive protein (CRP) were determined in healthy dogs (n = 15) and dogs with different diseases grouped as acute inflammation (I, n = 12), hematologic neoplasias (HT, including leukemia and lymphoma, n = 16), nonhematologic neoplasias (NHT, including epithelial, mesenchymal, and mixed, n = 20), and autoimmune hemolytic anemia (AIHA, n = 8). SAA and CRP were analyzed using commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a previous study in dogs, in which SAA was analysed in different neoplastic diseases, the serum concentration of the protein was not different between patients with lymphoma and leukaemia. 35 It is therefore plausible that SAA may be correlated with specific locations of the disease associated with different biological behaviour, such as nasal forms of the tumour, but does not give any additional information regarding disease stage. However, the number of patients in our staging group was small, with a low number of patients divided into the different groups; therefore, larger studies are necessary to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in dogs, in which SAA was analysed in different neoplastic diseases, the serum concentration of the protein was not different between patients with lymphoma and leukaemia. 35 It is therefore plausible that SAA may be correlated with specific locations of the disease associated with different biological behaviour, such as nasal forms of the tumour, but does not give any additional information regarding disease stage. However, the number of patients in our staging group was small, with a low number of patients divided into the different groups; therefore, larger studies are necessary to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer and inflammation are associated in a way that some cancers arise at the sites whereas the cancer induces an inflammatory microenvironment. We could support that CRP is a sensitive marker that has been shown to increase in response to malignancies [ 19 , 26 ] such as lymphoma [ 18 , 52 ], multiple myeloma [ 53 ], pancreatic cancer [ 54 ], and SCC [ 55 ]both in humans and dogs. In most studies, CRP levels were found to be highly elevated in patients with cancer and metastasis compared with the healthy control group or benign conditions [ 26 , 27 , 56 ].…”
Section: Discussionmentioning
confidence: 81%
“…However, as a biomarker it is not disease specific. 3,[11][12][13] Coupling biomarkers for rapid cell proliferation and inflammation has a strong relevance to the neoplastic process and malignant transformation. Chronic inflammation has been shown to predispose a patient to the development of neoplasia.…”
Section: Tests For Lymphoma Veterinary Diagnostics Institute Tkcanine1mentioning
confidence: 99%
“…Haptoglobin levels can be influenced (increased) by corticosteroid administration. 13,19 cCRP is an APP produced in the liver as part of the rapidly reacting first line of APPs induced by interleukin-1-type cytokines. Its serum levels are characterized by a dramatic increase within 4 hours after the inflammatory stimulus and rapid normalization.…”
Section: Sensitest/petscreen/tri-screen/canine Lymphoma Blood Testmentioning
confidence: 99%
See 1 more Smart Citation